Management of Haemophilic Pseudotumor of Left-Hand in A Paediatric Patient: a Case Report - Hancoro, Udi Heru Nefi; Siswanto, Totok; Dzulfikar, Muhammad (Indonesian Health Journal, 2024)
Hemophilia is a recessively inherited genetic disorder that causes abnormalities in the blood clotting process, which can lead to bleeding that is difficult to stop. One of the rare but significant complications of hemophilia is hemophilia pseudotumor, which occurs in 1-2% of hemophilia A and B patients. This study aims to analyze and evaluate the management of pseudotumor hemophilia. This study aims to analyze and evaluate the management of hemophilia pseudotumor in pediatric patients, focusing on the case of an 8-year-old boy who developed a pseudotumor in the left hand area due to hemophilia A. This case involves a boy with a history of hemophilia A who developed swelling of the left hand after experiencing trauma. Diagnosis was done through clinical examination, radiology (X-ray and MRI), and hematology evaluation. Treatment was factor VIII therapy, tranexamate, and amputation, as well as rFVIIa for bleeding prevention. The patient showed improved function after left hand amputation. Although conservative management can be considered for newly formed pseudotumors, in this case, a surgical approach was necessary due to the significant size and complications. Hemophilic pseudotumors can cause damage to surrounding tissues and require a multidisciplinary approach for management. Hemophilic pseudotumor is a rare but serious complication in people with hemophilia. Appropriate management, including surgical intervention, can improve the functional outcome of patients, despite the significant risks involved. Further research is needed to develop more effective treatment protocols.